Use of biphosphonates in pediatric nephrology biphosphonates in pediatric [Bifosfonatlarin pediatrik nefrolojide kullanimi pediatride bifosfonatlar] - (:unkn) unknown (My University, 2011)
Biphosphonates (BP), synthetic analogues of inorganic pyrophosphate, potently inhibit skeletal resorption by suppressing the recruitment and activity of osteoclasts and shortening their life span and decreasing bone loss. They are now well established as the major drugs used for the treatment of bone disease associated with excessive resorption such as Paget's disease, metastatic bone disease and osteoporosis, and refractory hypercalcemia in adults. Over the past decade, BP use in patients with various forms of kidney disease has become widespread. Increasingly, BP are being administered to children and have been reported to improve clinical outcomes and augment bone mass in conditions such as osteogenesis imperfecta, juvenile osteoporosis and fibrous dysplasia. There have been few clinical trials in children to treat bone loss, such as in glucocorticoid-induced osteoporosis and renal osteodystrophy, resulting from renal disease or rheumatologic conditions. The aim of this review was to evaluate the currently available evidence for the effectiveness and safety of BP in children with renal and rheumatological diseases.
Keywords: Biphosphonate; Children; Osteoporosis; Renal disease